THE EFFECT OF SMOKING DURATION ON THE QUALITY AND DHA COMPOSITION OF MILKFISH (Chanos chanos F) - Fronthea Swastawati (JOURNAL OF COASTAL DEVELOPMENT, 2004)
Milkfish contains omega-3 fatty acids (DHA), which is very important to maintain the health of human being. The research is mainly aimed to evaluate the reduction of DHA composition during smoking process. Organoleptic value of the product i.e. : 8,1 for fresh fish; 8,59 for smoked fish A (3 hrs smoking duration) and 8,78 for smoked fish B (5 hrs smoking duration). The composition of fish changes normally i.e. moisture content of 75,03% (fresh fish) decreases to 70,08% (A) and 68,11% (B). Protein composition increases from 20,30% (fresh fish) to 23,95% (A) and 27,50% (B). Lipid content increase from 0,61% (fresh fish) to 1,79% (A) and 3,53% (B). Ash content changes from 1,35% (fresh fish) to 2,03 (A) and 1,89% (B). SPSS analysis of DHA found of p < 0,05 means that A and B were significantly different. DHA content was found drastically decrease from 121,19 mg/100g (A) to 16,4 mg/100g (B). ANOVA result proved that there is an interaction between smoking duration and the composition of DHA. Smoking duration is recommended no longer than 3 hrs in order to maintain its quality and minimizing the reduction of DHA. hange :>p x pan>